ADVOCATE CODE OF CONDUCT FOR AGREEMENTS WITH CLIENTS BASED ON LAW NUMBER 18 OF 2003 - Andi Nur Fauziah (IAIN Bone, 2021)
The position of an advocate as a law enforcer is often referred to as an officer of the court. As Officer of the court, advocates must obey the rules in court; besides that, advocates must have an attitude that follows the dignity and dignity of the court so as not to tarnish the values of honour and dignity. Every lawyer must have work ethics. In carrying out their duties, an advocate needs to fulfil the limitations stipulated in Law Number 18 of 2003 concerning Advocates. However, the community is sometimes trapped in the stigma or the thought that hiring a legal expert or lawyer is very expensive and their ignorance of the judicial process so that many still ignore the law.This research is normative, empirical research wherein legal research examines the direct application of normative law (laws) to any particular law in society.